Modelling of lake—groundwater interaction in Turkey - Karaguzel, R.; Soyaslan, I. I.; Dogan, A. (Emerald, 2008)
A regional steady state groundwater flow model was developed for the Yalvac basin located in the watershed of Lake Egirdir, the second largest freshwater lake in Turkey. Determination of lake–groundwater interaction is an important step in taking proactive measures for optimal and beneficial use of water resources from the water management perspective. The geological structure around the lake and its surrounding aquifer system makes the modelling challenging. The hydrogeologic units in the groundwater system exhibit both confined/unconfined conditions: they are not horizontal, yet some of them are nearly vertical, which does not allow use of the ‘horizontal-layer’ concept of Modflow. The model demonstrated that it is a useful tool for planning and managing the water resources in the region by determining immeasurable components of classical water budget calculations, the groundwater inflow/outflow components, which are generally required for management of lakes. The groundwater discharge to Lake Egirdir through the Yalvac basin was estimated by means of the model. Two scenarios of hypothetical drought and wet conditions were simulated and evaluated from water resources management and groundwater–lake interaction perspectives.